A comprehensive skills catalogue for the raw materials sector and the structure of raw materials education worldwide. Issue 2 (2nd April 2020) - Hartlieb, Philipp; Jorda Bordehore, Luis; Regueiro y González-Barros, Manuel; Correia, Vitor; Vidovic, Jelena
ABSTRACT: The raw materials sector is undergoing significant structural changes. Skills required by emerging technologies and ever more challenging mineral deposits are changing quicker than todays' workforce can update them. Education mainly focusses on "classical" raw materials related topics (geology, mining and mineral processing), whereas there are deficiencies in emerging and non-technical skills like communication and management. There is a strong need for both sides to understand the necessities and constraints of the respective other partner in this business. This paper generates a knowledge base for future analysis of raw materials education, identifying currently taught skills and the structure of higher education. A definition of skills, knowledge and teaching areas is presented, leading to a comprehensive "skills catalogue". It builds the basis for an inventory of raw materials education worldwide.